The Integrating Local Wisdom In English Learning To Improve Pancasila’s Student Profile - Nur Cahya; Syafrizal Syafrizal (Universitas Mathla'ul Anwar Banten, 2022)
Language and culture are intertwined aspects that cannot be separated. Language is a manifestation of a developing culture. English is an universal language that is utilized in all countries as the language of communication. Learning it encourages students to speak and engage with people from all over the world, even if their cultural backgrounds are extremely different. Furthermore, the rapid development of the modernization era has decreased young people's enthusiasm for local wisdom. Given that local wisdom is the identity of a nation. Therefore, it is necessary to create an integrated English learning context with local wisdom in order to create a solid integrated learning in order to raise the profile of Pancasila students. The researcher wishes to conduct a literature review on the integration of local knowledge in English learning in order to raise the profile of Pancasila students. Learning English in integrated with local wisdom is one of the most authentic techniques of learning. In addition to employing teaching materials from the student's environment, this can raise the profile of Pancasila students in line with the Kurikulum Merdeka. This integration can assist teachers in becoming more creative in establishing teaching materials for English learners. It is expected that this step would shape and develop students' feelings of love and pride in the preservation of local wisdom in the nation.